Local People Hospitality at Tourism Destination: A Study of Tokyo Metropolitan Train Customers - Bastaman, Aam; Yodfiatfinda, Yodfiatfinda (Journal of Entrepreneurship, Business and Economics, 2021)
This study analyses Tokyo metropolitan train customers' response to a foreigner’s request for help, analyses the motives of the response relates to Japanese culture, and finally analyses the influence of metropolitan life on local consumers hospitality relating to their response for a small help from foreigners. The research uses a qualitative approach. As many as 25 people (informants) at several points of the city of Tokyo accidentally were asked for a small help to support a foreigner to guide or at least to give information on directions, such as the name of places, stations, train directions and building/offices. Data collection was conducted in the Metropolitan Tokyo area from 1 December to 5 December 2015. For data analysis purposes, expert interviews had also been conducted with 2 Japanese who stay temporarily in Jakarta and 2 Indonesian who have lived in Japan. Results of the study indicated that most people (23 out of 25) responded positively to a foreigner’s request for help. The study indicates that train customers in metropolitan Tokyo are helpful and friendly to foreigners, despite their busy and tight schedules. Hospitality value is embedded in Japanese culture. Research paper Keywords: Metropolitan train customers;  Local people hospitality;  Tourism destination; Japanese culture; Metropolitan’s life Reference to this paper should be made as follows: Bastaman, A., & Yodfianfinda, Y. (2021). Local People Hospitality at Tourism Destination: A Study of Tokyo Metropolitan Train Customers. Journal of Entrepreneurship, Business and Economics , 9 (2), 96–112.